The essential tension : selected studies in scientific tradition and change - Kuhn, Thomas S. (University of Chicago Press, 1977)
""Kuhn has the unmistakable address of a man, who, so far from wanting to score points, is anxious above all else to get at the truth of matters.""--Sir Peter Medawar, Nature